2014
DOI: 10.2478/s13545-014-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical methods for estimation of toxicity of marine bottom sediments based on the Gdańsk Basin area

Abstract: Toxicity assessment of environmental compartments, in particular sediments as a highly complex matrix, provides a more direct way to assess potential adverse effects of pollutants present in a sample in contrast to chemical analysis estimating only a quantitative level of xenobiotics. Interactions between chemicals, formations of derivatives and the influence of chemical properties of sediments such as the organic matter content causing the intensified sorption of hydrophobic pollutants suggest that a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, weak or insignificant correlations between metal concentration in the sediments and response of organisms suggested that there are other factors that contribute to the toxicity of the sediments, such as organic compounds, e.g., PAHs, PCBs, PCDDs, and PCDFs (Jancewicz et al 2012 ; Urbaniak et al 2010 , 2013 ), and inorganic compounds, e.g., arsenic (Widziewicz and Loska 2012 ). Additionally, interactions between pollutants may result in antagonistic or synergistic toxic effects that are difficult to predict (Narracci et al 2009 ; Fu et al 2013 ; Witt et al 2014 ). The PERI application in the study also may explain the low value of the correlation coefficients between the metals and the response of test organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, weak or insignificant correlations between metal concentration in the sediments and response of organisms suggested that there are other factors that contribute to the toxicity of the sediments, such as organic compounds, e.g., PAHs, PCBs, PCDDs, and PCDFs (Jancewicz et al 2012 ; Urbaniak et al 2010 , 2013 ), and inorganic compounds, e.g., arsenic (Widziewicz and Loska 2012 ). Additionally, interactions between pollutants may result in antagonistic or synergistic toxic effects that are difficult to predict (Narracci et al 2009 ; Fu et al 2013 ; Witt et al 2014 ). The PERI application in the study also may explain the low value of the correlation coefficients between the metals and the response of test organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, stripe rust control is primarily achieved through the use of resistant cultivars (Chen, 2014) and fungicide sprays (Chen et al, 2013). However, the loss of resistance in wheat cultivars has been happening frequently due to rapid emergence of new virulent races in Pst (Chen et al, 2009;Hu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the chemical status of sediments is important for identifying the type, concentration, and source of chemical substances and their metabolites, but it does not always show data about the effect of the pollution on organisms, and it does not provide any information on the synergic and antagonistic factors and their bioavailability (Wadhia and Thompson 2007 ; Mankiewicz-Boczek et al 2008 ; Narracci et al 2009 ; Tuikka et al 2011 , Witt et al 2014 , Buruaem et al 2013 ; Baran and Tarnawski 2015 ). From the viewpoint of risk to the aquatic environment, it is important to determine to what extent pollution in sediments negatively impacts this environment, and if they may be considered as a stressor for organisms.…”
mentioning
confidence: 99%